A novel lightweight CNN approach for Bangladeshi sign language gesture recognition - Rahman, Aryan; Khan, Ahbab Ali; Shoumik, Tazwar Mohammed (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.